Konflikt polsko-ukraiński 1943–1947 w polskiej historiografii i debacie politycznej - Ksenicz, Igor (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The article aims at presenting the differences in the reception of Polish- Ukrainian conflict of 1943–1947 by Polish historians and politicians, as well as diffusion of the knowledge about the past with contemporary political activity. Firstly, different ideas of the relation between history and politics are described. Secondly, a presentation of three groups of Polish researchers, who study Polish-Ukrainian conflict of 1943–1947, is made. Finally, the analysis of a 2003 parliamentary debate is drawn. The topic of this debate was to commemorate victims of anti-Polish OUN-UPA (Organisation of Ukrainian Nationalists – Ukrainian Insurgent Army) action. These are the main conclusions of the article: historical disputes are reflected in politics; the knowledge about Polish victims of OUN-UPA has been disseminated in the Ukraine thanks to the actions of Polish politicians.The article aims at presenting the differences in the reception of Polish-Ukrainian conflict of 1943–1947 by Polish historians and politicians,as well as diffusion of the knowledge about the past with contemporarypolitical activity. Firstly, different ideas of the relation betweenhistory and politics are described. Secondly, a presentation of threegroups of Polish researchers, who study Polish-Ukrainian conflictof 1943–1947, is made. Finally, the analysis of a 2003 parliamentarydebate is drawn. The topic of this debate was to commemorate victimsof anti-Polish OUN-UPA (Organisation of Ukrainian Nationalists– Ukrainian Insurgent Army) action. These are the main conclusionsof the article: historical disputes are reflected in politics; the knowledgeabout Polish victims of OUN-UPA has been disseminated in theUkraine thanks to the actions of Polish politicians.